The Effect of Problem Based Learning (PBL) Model on Students’ Critical Thinking Skills and Responsibility Attitudes in Linear Motion at MAN 1 Kota Jambi - nurjanah, kuswatun; Sukarno, Sukarno; Suryanti, Krisna (Science and Mathematics Education Journal, 2025)
The purposes of this research to determine the effect and relationship of the Problem Based Learning (PBL) model on students’ critical thinking skills and responsibility attitudes in Linear Motion at MAN 1 Kota Jambi. This research employs a quantitative method with a quasi-experimental design, the sample consists of two eleventh-grade classes of 53 students selected using Simple Random Sampling. The data collection instruments include tests on critical thinking skills and questionnaires on responsibility attitudes. Data analysis used inferential statistics with MS Excel and IBM SPSS 23. The N-gain test results indicate that the critical thinking skills of students in the experimental class had a score of 0.39 and 0.32 in the control class. Meanwhile, the N-gain score for responsibility attitudes in the experimental class was 0.44 and 0.35 in the control class. These findings suggest the PBL model is more effective in enhancing critical thinking and responsibility. The paired T-test results show a significance value of 0.000 < 0.05, meaning to rejecting the null hypothesis H0 and acceptance of the alternative hypothesis H1. Thus, the Problem-Based Learning (PBL) model has an effect and relationship on students’ critical thinking skills and responsibility attitudes in Linear Motion at MAN 1 Kota Jambi.